2017
DOI: 10.1089/biores.2017.0016
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the One-Carbon Cycle Restores Ovarian Reserve in Subfertile Women: Absence of Correlation with Urinary Bisphenol A Concentration

Abstract: Environmental endocrine disrupting chemicals (EDCs), including bisphenol A (BPA), induce DNA methylation errors and oxidative stress, and alter fertility. Animal studies have demonstrated that supporting the one-carbon cycle (1-CC) with appropriate dietary supplements can reduce the effects of EDCs. Anti-Mullerian hormone (AMH), a marker of ovarian functionality, has been tested in subfertile female patients, to control this hypothesis in humans. Fifty-five women with a history of 3–7 years of infertility, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…A combination of micronutrients similar to the one here tested administered to infertile women with low ovarian reserve achieved a significant increase of their AMH level and resulted in improved fertility with spontaneous pregnancies occurring in ladies waiting for oocyte donation [26]. Aiming to confirm this effect also in PCOS ladies, we included AMH among the tested parameters and found that also in our study, the treatment group recorded an increase of the AMH level.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A combination of micronutrients similar to the one here tested administered to infertile women with low ovarian reserve achieved a significant increase of their AMH level and resulted in improved fertility with spontaneous pregnancies occurring in ladies waiting for oocyte donation [26]. Aiming to confirm this effect also in PCOS ladies, we included AMH among the tested parameters and found that also in our study, the treatment group recorded an increase of the AMH level.…”
Section: Discussionsupporting
confidence: 65%
“…A total of 33 PCOS ladies (mean age 26.8, range [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] were enrolled between June 2017 and October 2018, and one patient withdrew her participation for personal reasons after the basal visit. Out of 32 patients randomized, 22 entered the active treatment group, and 10 the no treatment group.…”
Section: Resultsmentioning
confidence: 99%
“…Following the work on the impact of MTHFR C677T and A1298C isoforms on male [16] and female gametes [2], it was decided during fall 2016 to study patients with normal caryotypes that had a long history (at least 4 years) of recurrent miscarriages or infertility.…”
Section: Methodsmentioning
confidence: 99%
“…Also it regulates the balance between folates for nucleotide synthesis and those for methionine synthesis. Support of the 1-CC has demonstrated to be efficient for both male and female gametes [2][3][4][5]. MTHFR isoforms are well-known genetic variants impairing the efficacy to form 5-MTHF and eventually the methylation process.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy may also be beneficial via increasing the efficiency of DNA repair. It can solve some idiopathic infertility problems (Dattilo, Giuseppe, Ettore, & Ménézo, ; Silvestris et al, ) probably related to undetected/undefined environmental problems affecting methylation processes.…”
Section: Dna Methylation Errors and Osmentioning
confidence: 99%